Modelagem e desenvolvimento de prótese de mão mecatrônica com acionamento individual de dedos - (:unkn) unknown (Universidade Federal de Goiás, 2017)
Among the parts of the body, the hand is one of the most important for the humans because of their versatility and ability to manipulate objects. Many people do not have this member, either congenital malformation or necessity of amputation which make their day by day hardy. The existing comercial prosthesis have high costs making it inusual for a signifcative part of patients, on the other hand, there are at Internet communities to develop more accessible hand prostheses, for manufacturing by 3D printing but, It generally use unefficient activation methods. The target of this study is to develop the mechanical structure of a prosthesis hand with individual drive for each fingers, which can be make by using 3D printing, making it the most accessible price and the most efficient prosthesis when compared with current ones. For this, a mathematical model that describes the motion of the robotic finger will be determined. This finger has as actuator, DC motors, coupled to gears which in by their self are coupled in arms. The results will be checked by comparing the movements performed bettewen a prototype of the prosthesis and the determined mathematical model. It is expected that the prosthesis proposed by this research is the structural base for future stages of the development of a full prosthesis activated by voice command.
Modeling and development of mechatronic hand prosthesis with individual actuator finger
Keywords: Prótese de mão; Manufatura aditiva; Modelagem; Baixo custo prosthetic hand; Additive manufacturing; Modeling; Low cost; PROJETOS DE MAQUINAS::METODOS DE SINTESE E OTIMIZACAO APLICADOS AO PROJETO MECANICO